THE EFFECT OF INDIVIDUAL CHARACTERISTICS, WORK CULTURE, TEAMWORK, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT THE REGIONAL SECRETARIAT OF KARIMUN REGENCY - Yuslinda, Yuslinda; Indrayani, Indrayani; Khaddafi, Muammar; Catrayasa, I Wayan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Human resources are important in an organization or agency if they have an active and quality nature. So that organizational goals can be achieved easily if they are encouraged by increasing the potential of their human resources, in a government agency the Regional Secretariat of Karimun Regency is also very necessary, with increasing employee performance on individual characteristics, work culture, teamwork, work discipline, and motivation factors that become benchmarks for employees in carrying out their obligations at work. The research uses a quantitative approach. The result of this research is that all X variables have an indirect effect, which has a greater value than the variables that directly affect employee motivation and performance. The greatest indirect effect is work discipline with a total of 2873. According to the data managed it shows the R-square value of the Performance variable of 0.148. The R-square value of 0.148 means that the variability of the Performance construct which can be explained by the Variability of Motivation is 14.8% while the remaining 85.2% is influenced by other variables outside those studied, which means that the influence of all exogenous constructs of all variables X on Y is weak. The R-square value of the Motivation variable is 0.720. The R-square value of 0.720 means that the variability of the Motivation construct can be explained by the variability of the construct of all X variables of 72.06% while the remaining 28% is influenced by other variables outside the one studied, which means the influence of all exogenous constructs of all X variables on Z including very strong.